Physical space and its impact on waste management in the neonatal care setting. Issue 4 (July 2014) - Nichols, Andrew; Manzi, Sean
This paper reports an investigation intended to obtain some understanding of how the working environment might influence the practice and knowledge of those involved in the management of healthcare waste. The National Health Service (NHS) has a continuing waste problem, and the way it manages waste harms the environment and consumes resources. It has been estimated that the carbon footprint of the NHS in England is approximately 20 million tons of CO2 e. It has been suggested that better waste segregation could lead to more effective recycling, saving up to 42, 000 tonnes of CO2 . This qualitative study employed non-participant observation and semi-structured interviews. The interviews were carried out with the key informants within the participating neonatal intensive care unit. Findings from this study indicate that space and the physical arrangement of the environment are significant and influential factors in clinical practice. Where the clinical environment is not supportive, poor infection control and waste management practice is likely to occur. However, proximity of staff caused by a lack of physical space might facilitate situated learning and a collective development of knowledge in practice. The implementation of sustainable waste management practices would be more likely to succeed in an environment that facilitates correct waste segregation.